DCUN1D5 is a prognostic biomarker and correlated immune infiltrates and glycolysis in lung adenocarcinoma - Song Zhao; Xiaoli Han; Jingtao Huang; Jingxiong Zheng; Baoshan Zhao; Zongying Liang (Scientific Reports)
Abstract DCUN1D5 is up-regulated and promotes tumor progression in many cancers such as laryngeal squamous cell carcinoma and breast cancer, but the expression of DCUN1D5 in lung adenocarcinoma and its molecular mechanism are not clear. The differences of DCUN1D5 expression between lung adenocarcinoma and normal tissues were compared by TCGA, GEO and UALCAN databases, and the relationship between DCUN1D5 expression and clinicopathological features of patients was analyzed. The diagnostic and prognostic value of DCUN1D5 in patients with LUAD was analyzed by TCGA, GEPIA and Kaplan–Meier Plotter database. nomogram was constructed to predict the survival probability of patients. The GO, KEGG and GSEA enrichment analysis of DCUN1D5 co-expression genes were completed by R software. R software and GEPIA2 database were used to analyze the relationship between DCUN1D5 expression level and glycolysis-related genes and immune cell infiltration in patients with LUAD. The effects of interfering DCUN1D5 on the biological function and glycolysis level of lung adenocarcinoma cells were evaluated in vitro. The effect of down-regulation of DCUN1D5 on tumor formation in nude mice was studied in animal experiments. The expression of DCUN1D5 was increased in many kinds of tumors, and the expression in lung adenocarcinoma was significantly higher than that in normal tissues. The expression of DCUN1D5 was significantly correlated with TNM and pathological stage. DCUNN1D5 can play a diagnostic role in patients with LUAD and the prognosis of patients with high expression of DCUN1D5 is poor. Functional enrichment of DCUN1D5 co-expression genes involves a variety of biological processes. There is a strong correlation between DCUN1D5 and most glycolysis related genes. In addition, DCUN1D5 also affects tumor immune cell infiltration. In vitro experiments showed that the ability of cell proliferation, migration, invasion and glycolysis were significantly decreased and the ability of apoptosis was enhanced after down-regulation of DCUN1D5. Animal experiments showed that the tumor weight of nude mice decreased significantly after down-regulation of DCUN1D5. DCUN1D5 can be used as a biomarker for diagnosis and prognosis in lung adenocarcinoma. Down-regulation of DCUN1D5 can significantly affect the biological behavior of lung adenocarcinoma cells, which may be related to glycolysis and immune cell infiltration.